1996
DOI: 10.1021/bi960633j
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Orientation of Gla and EGF Domains in Coagulation Factor X Is Altered by Ca2+ Binding to the First EGF Domain. A Combined NMR−Small Angle X-ray Scattering Study,

Abstract: Coagulation factor X is a serine protease containing three noncatalytic domains: an N-terminal gamma-carboxyglutamic acid (Gla)1 domain followed by two epidermal growth factor (EGF)-like domains. The isolated N-terminal EGF domain binds Ca2+ with a Kd of 10(-3) M. When linked to the Gla domain, however, its Ca2+ affinity is increased 10-fold. In this paper, we present the NMR solution structure of the factor X Gla-EGF domain pair with Ca2+ bound to the EGF domain, as well as small angle X-ray scattering (SAXS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
69
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 69 publications
6
69
0
1
Order By: Relevance
“…These observations are in agreement with a number of studies where it was demonstrated that conformational changes in structure can be associated with calcium ion binding, e.g. troponin C (41), fibrillin-1 (42,43), and the clotting factors IX and X, as well as the complement component C1r, where there is a change in orientation or alignment of domains (44,45). Furthermore, the conserved carboxylate residues contained in the EGF domain that are responsible for binding calcium ions with high affinity (D/N)X(D/N)(E/Q)(X) m (D/N)*(X) n (Y/F) (see Ref.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These observations are in agreement with a number of studies where it was demonstrated that conformational changes in structure can be associated with calcium ion binding, e.g. troponin C (41), fibrillin-1 (42,43), and the clotting factors IX and X, as well as the complement component C1r, where there is a change in orientation or alignment of domains (44,45). Furthermore, the conserved carboxylate residues contained in the EGF domain that are responsible for binding calcium ions with high affinity (D/N)X(D/N)(E/Q)(X) m (D/N)*(X) n (Y/F) (see Ref.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, we propose that a hairpin conformation of mTld holds the CUB4 and -5 domains in locations that exclude substrates cleavable by BMP-1 or limit their access to the active site. Indeed, binding of Ca 2ϩ by an isolated EGF domain has been shown to result in little effect on its conformation; instead changes appear to have longer range effects involving neighboring domains (44,45). Taken together, our data imply a role of the two C-terminal CUB in regulating the enzymatic activity of mTld by a substrate-exclusion mechanism.…”
Section: Discussionmentioning
confidence: 63%
“…A Ca 2ϩ -dependent interaction between the EGF-like and Gla modules appears to enhance the affinity of the site on the EGF-like module to the point that it is tighter (17, 18) (k d ϳ 120 M) than the catalytic domain site. Consistent with this, nuclear magnetic resonance shows that Ca 2ϩ binding tightens the fold of the isolated EGF N domain and bends Gla and EGF N domains toward each other around a hinge located in the Gla domain, referred to as a helical or hydrophobic stack (19).…”
mentioning
confidence: 62%
“…In terms of secondary structure, this translated into a large increase in ⌰ 222 /⌰ 208 and a nearly insignificant decrease in ␣-helical content (Tables I and II). It is known from NMR studies that Gla-EGF N undergoes a significant structural reorganization in which the EGF and Gla domains fold onto each other upon binding Ca 2ϩ (19). C6PS induced a structural change in Gla-EGF N in the absence of Ca 2ϩ (⌰ 222 /⌰ 208 increased by 333% and helicity increased by 2.3%; Fig.…”
Section: Effect Of Soluble C6ps On the CD Spectra Of Expressed Human mentioning
confidence: 96%
See 1 more Smart Citation